Experimental Study of TiO2 Nanoparticles Fabrication by Sol-gel and Co-precipitation Methods for TiO2/SnO2 Composite Thin Film as Photoanode - Endarko, E.; Adawiyah, Siti Rabi’atul (Jurnal ILMU DASAR, 2019)
Sol-gel and coprecipitation methods successfully prepared titanium dioxide (TiO2) powders with anatase structure. The TiO2 powders are then used to fabricate pure TiO2 thin-film or mixed with SnO2 powders for the TiO2/SnO2 composite thin film. Furthermore, the structural, morphological, as well as the optical properties of films were also investigated. The results showed that the synthesized thin-film of TiO2 powders by sol-gel method obtained better crystallinity and microstructure compared to the synthesized thin film by co-precipitation method. In the DSSC system, these features are needed to increase the electron mobility that responsibility for transport and recombination of photoexcited electrons. SEM images exhibited the smooth surface and uniform in particle size obtained by the addition of SnO2 powders in composite films. The composite thin film also indicated a higher transmittance value. Keywords: sol-gel,co-precipitation,anatase, composite.